Kitaran harga dalam industri ternakan. - Maan, Normah; Yaacob, Yusof (Faculty of Science, 1994)
This paper discuss price and production model concerning a livestock industri which gives rise to a system of felay differential equations, as proposed by Larson[8]. In this model it is assumed that the demand curve is liunera , a lag between planned and (and propotional to) realized production, and that the rate of change of breeding is propotional to the derivation of price from equilibrium. We prove that there exists sinusodial solutions, which shows that exists price cycle in livestock industries, as conjectured by Larson. The sinusodial solutions can be obtained by using the method of step.